THE EFFECTIVENESS OF ELECTROACUPUNCTURE, ACUPRESSURE AND MASSAGE COMBINED WITH SHOCKWAVE FOR THE TREATMENT OF CERVICAL RADICULOPATHY CAUSED BY SPINAL DEGENERATION (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluation of the analgesic effect of electroacupuncture, acupressure and massage combined with shockwave therapy in the management of cervical radiculopathy caused by spinal degeneration.Subjects and methods: 60 patients aged 40 and over who were diagnosed with cervical radiculopathy due to spinal degeneration at the National Hospital of Acupuncture. This was a clinical intervention, comparing before and after treatment, with a control group. Patients diagnosed with cervical radiculopathy due to spinal degeneration were divided into two groups, both groups were treated with electroacupuncture, acupressure massage according to the Ministry of Health’s protocol for 20 consecutive days, The patients in research group was additionally treated with shock waves 2 times per week, 6 times in 20 days.Results: After 20 days of treatment, the average VAS score of the research group decreased from 5.30 ± 0.65 points to 1.30 ± 0.79 points and decreased more than the control group (from 5.13 ± 0.86 points to 1.87 ± 0.63 points) with p < 0.05; the neck disability index score of the study group decreased from 19.63 ± 9.58 points to 5.93 ± 3.97 points, which was a greater reduction compared with the control group from 20.33 ± 7.53 points to 13.50 ± 6.02 points, with p < 0.05.Conclusion: Electroacupuncture, acupressure and massage combined with shock waves are effective in pain relief in the patients with cervical radiculopathy caused by spinal degeneration.
Keywords: Electroacupuncture, massage acupressure, shockwave, cervical radiculopathy.